Meta-Analysis: Effect of Bullying on the Risk of Suicide in Adolescents - Aprilia, Sholikha Dela; Prasetya, Hanung; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Mental health disorders are among the most important public health problems globally. Bullying affects the lives of many children and young people. Studies in high-income countries have reported an association between bullying and suicidal behavior among school adolescents. For example, studies in various parts of the United States found that students who were bullied were significantly more likely to experience suicidal ideation, planning, and suicide attempts. This study aims to determine the effect of bullying on the risk of suicide in adolescents Subjects and Method: The meta-analysis was carried out according to the PRISMA flow chart and the PICO model. Q: Adolescent, I: Bullying , C: Not bullying, O: Risk of suicide. Search for articles in this study through databases that include PubMed, Google Scholar, Science Direct and Scopus. With keywords including: